Badania ankietowe konsumentów na pograniczu polsko-niemieckim w warunkach rynku europejskiego - Witek, Jolanta; Błoński, Krzysztof (Questionnaire Research of Consumers on Polish-German Borderland in the Conditions of European Market, 2006)
From among many factors which influence the estimation of the accession of Poland to the European Union, the proximity of living at the border plays an important part. The border has become an important economic factor for people living there in the range of its traffic, which in the greater range than in other parts of the country lets acquire and consume the neighbours' goods as well as develop the economic activity in the sphere of small and medium enterprises.I The paper contains the estimation of influencing of the process of the integration of Poland with the European Union living in the border line, carried out on the ground of chosen questionnaire surveys.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 309-319